A Drink to Prevent Meningitis (2011)
Expeditionaries and mentors worked on which plants help cure and prevent diseases that affect babies' nervous system. Plasmebex (plants, meningitis and babies) is a drink based on arrayan, toronjil and avocado leaves, the result of research by one of the groups interested in health and life sciences.